Studi Sistem Dispersi Padat Meloksikam Menggunakan Hiroksipropil Metilselulosa (HPMC) 6 Centipoise (CPS) - Erizal Zaini; Maria Dona Octavia; Kiki Rizky Wirza (Jurnal Farmasi Higea, 2012)
The solid dispersion system of meloxicam-hydroxypropyl methylcelluloce (HPMC) 6 centipoise (cps) had been studied. The solid dispersion system was prepared by solvation method with several combination of meloxicam and HPMC were 1:1, 1:3 and 1:5. The physical mixture of meloxicam and HPMC with similar composition were used as standard. The powder of solid dispersion system and physical mixture were evaluated by X-ray powder diffraction, thermal (DTA), SEM and FT-IR spectroscopy analysis. The dissolution studies were carried out in USP type II apparatus. The result of X-ray powder diffraction analysis showed that the solid dispersion of  meloxicam with HPMC decreased the drug crystallinity. The endothermic peak of meloxicam from solid dispersion products shifted to lower temperature and peak intensity decreased significantly. X-ray powder diffraction and DTA indicated transformation of crystalline state of meloxicam to amorphous one by solid dispersion with HPMC. SEM results showed the solid dispersion of meloxicam and HPMC has agglomerates form. FT-IR spectra indicated no chemical interaction between meloxicam and HPMC in the solid dispersion. The highest in dissolution rate was observed with solid dispersion products of meloxicam and HPMC with ratio 1:5 (94,083 %) compared to pure meloxicam and its physical mixture.